Pemanfaatan Limbah Cangkang Telur Sebagai Pupuk Organik Pada Tanaman Berbuah Di Desa Kuranji Kabupaten Lombok Barat - Nikhla Fitriyah; Nining Purwati; Meilinda Pahriana Sulastri (Bhakti: Jurnal Pengabdian Masyarakat, 2024)
People often underestimate egg shell waste, even though egg shell waste contains many benefits, one of which is that it can be used as organic fertilizer for plants. Egg shells contain the nutrients calcium, magnesium and phosphorus which are really needed by fruit-bearing plants so that the fruit is healthy, dense and does not rot quickly. The aim of implementing this community service is to provide understanding to the community about the importance of processing egg shell waste into useful products such as organic fertilizer to increase environmental awareness. The method for implementing community service activities located in Kuranji Village, Labuapi District, West Lombok Regency is by explaining the process of making organic fertilizer from egg shells. The results achieved are that people become more concerned about the environment by starting to collect egg shell waste and use it as fertilizer and can find out the contents and benefits of egg shells. There are 3 ways to make fertilizer from egg shells that can be useful for fruit-bearing plants, namely the first is using egg shells that have been mashed using a blender, then the second way is to use boiled water from eggs, and the last is mashed egg shells mixed with vinegar. along with water and then sprinkle it on the plants. The plants used as examples are tomatoes, chilies and bananas.